2018
DOI: 10.1055/a-0774-8809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Supplementation on Prostate Cancer: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Vitamin D has received attention for its potential to disrupt cancer processes. However, its effect in the treatment of prostate cancer is controversial. This study aimed to assess the effect of vitamin D supplementation on patients with prostate cancer. In the present study, PubMed, Scopus, ISI Web of Science, and Google Scholar were searched up to September 2017 for trials that evaluated the effect of vitamin D supplementation on prostate specific antigen (PSA) response, mortality, and its possible side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 71 publications
2
14
0
2
Order By: Relevance
“…Based on the aforementioned trials and the findings of a relevant systematic review by Petrou and associates [ 152 ], most RCTs suggested a lack of efficacy of vitamin D ONS in reducing PSA concentrations among men harboring PCa. These findings were also corroborated by a more recent meta-analysis, indicating a non-significant difference in PSA change, PSA response proportion and mortality rate between men with PCa receiving vitamin D, as compared with those randomized to a placebo [ 153 ].…”
Section: Antioxidants and Psa Kineticssupporting
confidence: 58%
“…Based on the aforementioned trials and the findings of a relevant systematic review by Petrou and associates [ 152 ], most RCTs suggested a lack of efficacy of vitamin D ONS in reducing PSA concentrations among men harboring PCa. These findings were also corroborated by a more recent meta-analysis, indicating a non-significant difference in PSA change, PSA response proportion and mortality rate between men with PCa receiving vitamin D, as compared with those randomized to a placebo [ 153 ].…”
Section: Antioxidants and Psa Kineticssupporting
confidence: 58%
“…As to Vit D status, median levels showed seasonal but also regional dependence in line with previous research [7,11,12]. Stratification by median Vit D plasma levels revealed lower values in smokers and overweight patients, which is supported by findings from other studies [7,[13][14][15], but the observed relationship between Vit D, PSA, and selenium plasma levels is less clear [7,16,17]. In contrast to data from select studies, our analysis [18] failed to show significant differences in pathologic outcomes according to circulating levels of Vit D. However, published prospective data on blood Vit D and PCa risk are limited and not comparable with Vit D status prior to RP [7].…”
Section: Discussionsupporting
confidence: 85%
“…As recently emerged, contradictory data are reported about the effects of vitamin D supplementation in prostate cancer progression [114]. Although calcitriol is used in the management of patients with secondary hyperparathyroidism in renal insufficiency [111], its administration at high doses has been reported in patients with prostate cancer.…”
Section: Vitamin D and Cancer: Epidemiological Evidencementioning
confidence: 99%